1998
DOI: 10.3354/meps168163
|View full text |Cite
|
Sign up to set email alerts
|

Tentacle structure and filter-feeding in Crisia eburnea and other cyclostomatous bryozoans, with a review of upstream-collecting mechanisms

Abstract: ABSTRACT-The upstream-collecting filter-feeding mechanisms occurring in many aquatic organisms are not adequately descnbed. Tentacles of Crisia eburnea and other cyclostome bryozoans, with only lateral and laterofrontal ciliary bands, are among the least complicated upstream-collecting systems among metazoans. SEM and TEM revealed that the tentacles have 2 rows of very closely set lateral cilia and 1 row of stiff laterofrontal cilia on each side. The shape of the basal membrane and the longitudinal muscles ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 25 publications
6
104
1
1
Order By: Relevance
“…However, identification of a Post2 class Hox gene from the bryozoan Bugula 94 turrita, as described in Chapter 4, provides strong evidence for a close relationship between bryozoans and other lophotrochozoans, upholding the phylogenetic validity of the clade as it was initially defined. These finding are consistent with recent work questioning the homology of the bryozoan tentacles to the lophophore of brachiopods and phoronids (Nielsen and Riisgård, 1998). It is therefore suggested that, to avoid the suggestion of homology, the term "lophophore" be reserved only for the tentacular feeding structure of phronids and brachiopods, and not that of bryozoans.…”
Section: Srkk-cp---f ---------Ly -M----e--y --Sqhv-----v ----------M--mssupporting
confidence: 81%
“…However, identification of a Post2 class Hox gene from the bryozoan Bugula 94 turrita, as described in Chapter 4, provides strong evidence for a close relationship between bryozoans and other lophotrochozoans, upholding the phylogenetic validity of the clade as it was initially defined. These finding are consistent with recent work questioning the homology of the bryozoan tentacles to the lophophore of brachiopods and phoronids (Nielsen and Riisgård, 1998). It is therefore suggested that, to avoid the suggestion of homology, the term "lophophore" be reserved only for the tentacular feeding structure of phronids and brachiopods, and not that of bryozoans.…”
Section: Srkk-cp---f ---------Ly -M----e--y --Sqhv-----v ----------M--mssupporting
confidence: 81%
“…In most bryozoans, three types of ciliary rows may be found on the tentacles: lateral, frontal, and laterofrontal. Lateral cilia produce the feeding currents of the lophophore (Gordon et al 1987;Nielsen 1987. When the through currents pass between the tentacles, they form a relatively strong core current directed straight down the lophophore to the mouth.…”
Section: Capture Mechanismsmentioning
confidence: 99%
“…The present description of the catch-up principle further substantiates the hypothesis proposed by Strathmann and Leise (1979), who found that suspended particles are concentrated when they are ''overtaken'' by cilia in their effective stroke and ''pushed faster than the water.'' Ciliary upstream-collecting animals possess ciliary bands that divert suspended food particles from the main water current and concentrate them on the upstream side of the band (Bullivant 1968a;Strathmann 1971Strathmann , 1973Strathmann and Bonar 1976;Gilmour 1979Gilmour , 1982Gilmour , 1985Nielsen 1987Hart 1990Hart , 1991Hart and Strathmann 1994; for review, see Nielsen and Riisgård 1998). The capture mechanism is correlated with the presence of a single band of cilia, which appears to be responsible for both the water transport and particle retention.…”
Section: Capture Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations